Efficiency of 2-phenoxyethanol and Clove Oil for Reducing Handling Stress in Reared Meagre, Argyrosomus regius (Pisces: Sciaenidae) - Barata, Marisa (2017)
The effect of two anesthetics, 2-phenoxyethanol (2-PE) and clove oil (COil) were studied in meagre, Argyrosomus regius. This study aimed to determine the adequate dose of anesthesia for different aquaculture procedures, to assess a sedative or stressor effect of low anesthetic concentrations, and to assess the effect of low anesthetic doses at high fish densities for longer periods of time on fish survival and behavior. Anesthetics were tested at different concentrations: 2-PE at 100, 250, 400, 550, and 700mg/L; COil at 25, 40, 55, 70, and 85mg/L. Meagre became anesthetized within 10min when using concentrations above 250mg/L for 2-PE and above 40mg/L for COil. Deep anesthesia was achieved at 700 and 85mg/L, for 2-PE and COil, respectively. The fish did not react when blood was collected at these concentrations. Plasma cortisol and glucose levels were similar between sedated meagre with both 2-PE-100mg/L and COil-10mg/L, and the control (not sedated; P>0.05). This suggests that low concentrations of these anesthetics induce similar stress response as handling without anesthesia during routine activities. No mortality was registered when meagre was maintained at high densities with low concentrations of each anesthetic for 2h.